2023
DOI: 10.1021/acsaelm.2c01357
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Content-Addressable Memory Cells with IGZO Channel: Impact of Retention Degradation on the Multibit Operation

Abstract: Indium gallium zinc oxide (IGZO)-based ferroelectric thin-film transistors (FeTFTs) are being vigorously investigated for being deployed in computing-in-memory (CIM) applications. Content-addressable memories (CAMs) are the quintessential example of CIM, which conduct a parallel search over a queue or stack to obtain the matched entries for a given input data. CAM cells offer the ability for massively parallel searches in a single clock cycle throughout an entire CAM array for the input query, thereby enabling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…1f shows that both high and low conductance states are stable over time, implying the excellent retention performance, which is necessary for parallel computing in neural networks. 42 As is known, biological synapses transmit electrical or chemical signals from the front to the back end of the synapse by regulating the content of neurotransmitters, 43 as shown in Fig. 2a.…”
Section: Resultsmentioning
confidence: 99%
“…1f shows that both high and low conductance states are stable over time, implying the excellent retention performance, which is necessary for parallel computing in neural networks. 42 As is known, biological synapses transmit electrical or chemical signals from the front to the back end of the synapse by regulating the content of neurotransmitters, 43 as shown in Fig. 2a.…”
Section: Resultsmentioning
confidence: 99%
“…However, Si channel in the metal-ferroelectric-semiconductor (MFS) ferroelectric transistor, an amorphous SiO 2 interfacial layer (SiO 2 –IL) is easily formed between an HZO film and Si, which could cause stress relaxation, whereas a Si substrate is expected to play a role as a tensile stressor to HZO films during an annealing process. Furthermore, it has been reported that MFS structures require a high-temperature process (>400 °C) to achieve robust ferroelectricity. , This high temperature potentially leads to the excessive growth of SiO 2 at the interface and causes reliability issues on MFS capacitors and FeFETs. , Moreover, high process temperature also poses limitations for low thermal budget applications (e.g., 3D integration and flexible electronics) that require channel materials like oxide semiconductors. A new idea was proposed by Onaya et al using a ZrO 2 nucleation layer to form the HZO film with the ferroelectric o-phase in an MFS structure . This concept is based on the superior characteristics of ZrO 2 films processed via the low-temperature ALD process at 300 °C (e.g., good crystallinity and predominantly o/t/c-phases).…”
Section: Interface Engineeringmentioning
confidence: 99%
“…Even though a typical CAM cell comprises two SRAM cells, each of which has six to eight transistors and results in high energy consumption and poor density, FeFETbased high-density, low-footprint CAM cells have been shown in many recent studies. [24][25][26][27][28][29][30] FeFET-based CAM cells are a serious contender for being deployed as storage-class memory in the memory hierarchy due to fast switching, low-read latency, high density, sufficient read and write endurance, negligible sneak path current, linearity, and high data-retention ability. FeFET-based CAM architecture offers a few hundred nanoseconds write latency, and lowenergy consumption during the data search operation, and recent reports of logic-compatible FeFETs [31][32][33][34] have fueled this concept of FeFET-CAM-based SCM section further.…”
mentioning
confidence: 99%
“…However, the primary hindrances to implementing FeFETbased CAM cells as SCM are concerns regarding device variation, retention degradation, and temperature sensitivity, which have been a focus in many works in literature in recent times. [9,24,[35][36][37][38][39][40] Although several methods have been investigated to improve the device variations and other nonidealities in FeFETs, it is one of the most vexing research topics in FeFETs to date. [41][42][43][44][45][46] In this work, we focus on evaluating the impact of process and temperature variations on the performance of FeFET-based CAMs and gauging their suitability as SCM.…”
mentioning
confidence: 99%
See 1 more Smart Citation